The impact of the Japanese occupation on contemporary ethnic politics in Malaysia - Yakut, Neslihan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This study aims to analyze how the Japanese occupation of Malaysia, back then Malaya, created a post-war continuation in the formation of contemporary ethnic politics under Malay political primacy in Malaysia between 1945-1969. The brief Japanese occupation has ramped up the nationalist sentiments and political experiences of not only the Malays but also the Chinese and Indians, who were regarded as transient communities. The Japanese military experience of Malaysia between 1941 and 1945 brought dramatic political changes that were beyond the ability and expectations of pre-war colonial power of Malaysia: The British, which resulted in the decolonization of Malaysia. While independence was achieved as a result of the nationalist movements of all ethnic groups that emerged with the Japanese occupation, the Malays found room to actualize their nationalist agendas in fields of politics, economy, and nation-building. This study observes the role of Japan in the consolidation of ethnic politics in Malaysia under Malay etnocracy by predicating on the impacts of the Japanese invasion.